Evaluación de las capacidades, las percepciones y los resultados del programa de monitoreo campesino de las aves en la zona de amortiguamiento del Corredor Biológico Mesoamericano, Chiapas, México - Lowry, Jennifer, author (Colorado State University. Libraries, 2012)
Conservation corridors are important for maintaining a contiguous landscape and con provide refugia, resources and habitat microclimates for wildlife. Shade-grown coffee is an important agricultural crop that promotes connectivity in and around El Triunfo Biosphere Reserve, that is part of the Mesoamerican Biological Corridor in Chiapas, Mexico. Monitoring programs can be a tool to evaluate and enhance conservation success, as well as resource management on private land or communally managed ejido lands. As conservation efforts seek to build capacity for large-scale monitoring of the effectiveness of corridors, there is interest in seeing the degree to which citizen science monitoring programs could be an effective approach, at the site level up to the landscape and regional levels. This project evaluated data quality collected by campesino monitors on bird species, environmental perceptions, attitudes, and cobenefits resulting from a Citizen Science Monitoring Program initiated by a non-governmental organization, Pronatura Sur. Perceptions and attitudes regarding nature were transformed positively since implementation of the program. Many communities made hand painted signs that promote conservation. Results show that program design may need to be simplified to ensure better quality data and reduce potential bias and increase confidence in data, and that additional training is needed in conducting point counts. Species codes should not be used due to spelling errors, instead full scientific names should be written out. Reinforcing the concept of standardization is crucial to reduce bias. Supplying field guides on vegetation, as well as watches, can improve data quality. Monitor's perceptions and attitudes on nature were impacted, resulting in increased understanding of the environment and the need to conserve resources in this area. Monitors were evaluated through point count comparisons and surveys. Results of this project provided insight on the bird monitoring program, identified strengths and weaknesses, and acts as a lens for the iterative process to achieve the goal of strengthening conservation efforts in the multi-country Mesoamerican Biological Corridor.
Evaluation of capacities, perceptions, and results of a citizen science bird monitoring program in the buffer zone of the Mesoamerican Biological Corridor in Chiapas, Mexico
In both Spanish and English.
Keywords: puntos de conteo; el Corredor Biológico Mesoamericano; aves; café amigable con las aves; Café de Sombra; La reserva Biosfera El Triunfo; programa de monitoreo; campesino; científico ciudadano